Role of Teacher Understanding about Instructional Visual Aids in Developing National and International Student Learning Experiences - AlAli, Rommel Mahmoud; Al-Barakat, Ali Ahmad (Journal of International Students, 2023)
We investigated the understanding of the role of instructional visual aids in shaping the learning experiences of both national and international children among early childhood education teachers. To achieve this objective, a meticulously crafted questionnaire incorporating visual elements such as pictures and drawings was administered to a randomly selected sample of 220 participants. The instrument underwent rigorous validation procedures to ensure its reliability. The finding of the study highlights a prevalent misinterpretation among early childhood education teachers concerning the nuanced functions of visual aids in children's learning.